À propos de la tradition conradienne du Cœur des ténèbres comme archive internationale - Pierre Halen (Continents manuscrits)
Heart of Darkness, a both british and international work, forms the basis of the “conradian tradition”, consisting of regrowth of thematic and narrative elements originating from the initial story. In novels, media, documentaries, comics or movies, those components can be narrative or narratologic invariants, patterns related to space and landscape, or more abstracts topics as the Evil. The steamer, central symbol of progress, condense them and let appear what’s at stake : beyond the possible ideological appropriation by the anticolonialist discourse, Conrad’s story can be seen as a kind of modern parable about civilisation, whose heart is the “horror” of the History self.